Dimensions of compulsive exercise across eating disorder diagnostic subtypes and the validation of the Spanish version of the compulsive exercise test - Sauchelli, Sarah; Arcelus, Jon; Granero, Roser; Jimenez-Murcia, Susana; Agüera, Zalda; Del Pino-Gutiérrez, Amparo; Fernandez-Aranda, Fernando (Frontiers, 2016)
Objectives: Compulsive exercise in eating disorders has been traditionally considered as a behavior that serves the purpose of weight/shape control. More recently, it has been postulated that there may be other factors that drive the compulsive need to exercise. This has led to the development of the Compulsive Exercise Test (CET); a self-reported questionnaire that aims to explore the cognitive-behavioral underpinnings of compulsive exercise from a multi-faceted perspective. The objectives of this study were threefold: (1) to validate the Spanish version of the CET; (2) to compare eating disorder diagnostic subtypes and a healthy control group in terms of the factors that drive compulsive exercise as defined by the CET; (3) to explore how the dimensions evaluated in the CET are associated with eating disorder symptoms and general psychopathology.